Assessing the Satisfaction Levels in Simulation-Based Learning Among Students in Teaching Hospitals (International Journal of Environmental Sciences, 2025)
Background:Simulation-Based Learning (SBL) has emerged as a transformative approach in medical education, bridging the gap between theory and clinical practice in a safe, controlled environment. Understanding students’ satisfaction with SBL is essential for effective curriculum integration.Objectives:To assess the satisfaction levels among undergraduate medical students exposed to SBL and to identify challenges associated with its implementation.Methods:A cross-sectional observational study was conducted among 96 third- and final-year MBBS students at Sree Balaji Medical College, Chennai. Participants with prior exposure to simulation sessions were selected using purposive sampling. Data were collected using a pre-validated questionnaire covering two domains: overall satisfaction and perceived challenges. Responses were recorded on a 5-point Likert scale and analyzed using SPSS version 22. Inferential statistics including Chi-square and t-tests were applied.Results:The overall satisfaction with SBL was high (mean score 4.3 ± 0.6). Facilitator support, organization, and content relevance were highly rated. No significant difference in satisfaction was observed between third- and final-year students or between genders. However, students attending ≥3 sessions showed significantly higher satisfaction (p = 0.017). Common challenges included lack of realism (39.6%) and equipment constraints (33.3%). Lack of realism was significantly associated with lower satisfaction (p = 0.022).Conclusion:Students viewed SBL positively, citing it as engaging and educationally beneficial. Addressing realism, faculty training, and equipment limitations can further enhance the impact of simulation in medical education.